Measurement and Investigation on 1-D Consolidation Permeability of Saturated Clay considering Consolidation Stress Ratio and Stress History - Le Zhang; Faning Dang; Jun Gao; Jiulong Ding (Geofluids)
To study the influence of consolidation stress ratio and stress history on 1-D consolidation permeability of saturated clay, one-dimensional consolidation permeability tests were carried out with GDS triaxial device. The results indicated that the permeability coefficient and void ratio of normally and overconsolidated saturated clay decreased with the increase of consolidation stress ratio under different consolidation stress ratios but the same stress history. And the amount of final sample’s compression increased with the increase of the consolidation stress ratio. Under the condition of the same consolidation stress ratio but different stress history, the amount of final compression of the overconsolidated saturated clay was smaller than that of the normally consolidated saturated clay. Besides, the stress difference σdv between consolidation pressure σ and gravity stress σcz was fitted to the amount of the final sample’s compression, and a good linear relationship between the stress difference σdv and the amount of the final sample’s compression under each consolidation pressure was obtained. The results showed that it is necessary to consider the influence of consolidation stress ratio and stress history simultaneously on 1-D consolidation permeability of saturated clay. Meanwhile, it can accurately predict the amount of the final sample’s compression after knowing the gravity stress. Moreover, a model prediction analysis was conducted on the saturated clay and recommended to use the modified Kozeny-Carman’s equation to predict the permeability coefficient of Luochuan saturated clay during one-dimensional consolidation.